High-temperature-resistant light-weight thermal insulation material and preparation method thereof

CN123003302APending Publication Date: 2026-10-30ZHENGZHOU LEAF NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611302038.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但其在800°C的高温条件下长期服役时,纳米粒子表面活性高,会导致颗粒间烧结、孔隙率下降、导热系数急剧升高,绝热性能大幅退化

Benefits of technology

本发明的耐高温轻质保温材料以气相纳米SiO2粉为基体,通过加入适量的硅微粉和偏高岭土能够抵消或缓解保温材料整体的收缩内应力,稳定内部结构并提升材料整体的耐温能力,能够维持高温使用条件下的绝热性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003302A_ABST
    Figure CN123003302A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of high-temperature-resistant light thermal insulation materials, it relates to the technical field of refractory materials.The high-temperature-resistant light thermal insulation materials of the present application include 65~80wt% of fumed nano-SiO2Powder, 5~15wt% of silicon powder, 3~15wt% of metakaolin, 3~10wt% of high-silica glass fiber, and 1~5wt% of calcium aluminate cement.The high-temperature-resistant light thermal insulation materials of the present application take fumed nano-SiO2Powder as matrix, by adding appropriate amount of silicon powder and metakaolin, the shrinkage internal stress of thermal insulation material as a whole can be offset or alleviated, the internal structure is stabilized and the temperature resistance of material as a whole is improved, and the heat insulation performance under high-temperature use condition can be maintained.The present application also relates to a kind of preparation method of high-temperature-resistant light thermal insulation materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of refractory materials, specifically to a high-temperature resistant lightweight thermal insulation material and its preparation method. Background Technology

[0002] Lightweight insulation materials are key to achieving energy conservation, emission reduction, and safe operation in high-temperature kilns. Constructing an insulation layer composed of lightweight materials within the kiln lining effectively prevents heat loss through conduction. Replacing heavy refractory bricks with these lightweight insulation materials not only significantly reduces heat loss from the furnace body and accelerates heating and cooling rates, but also allows for thinner furnace walls and optimized kiln structure, resulting in significant overall energy savings. Some new materials can even achieve energy savings of over 50%.

[0003] As is well known in the industry, the core heat transfer suppression mechanism of constructing micro- and nano-scale porous structures within materials lies in the fact that when the pore size is smaller than the mean free path of gas molecules, collisions between the pore walls and gas molecules become dominant, effectively suppressing gas-phase heat conduction and convective heat transfer. This "nano-confinement" effect is particularly significant at high temperatures—as the temperature increases, the movement of gas molecules intensifies, but due to the confinement of the nanopores, their contribution to the increase in thermal conductivity is limited, allowing the overall thermal conductivity of the material to remain relatively stable over a wide temperature range, significantly better than conventional porous materials. Based on this principle, current thermal insulation materials are rapidly developing towards microporous and nanoporous structures. A typical example is silica aerogel, which possesses a nanoscale three-dimensional continuous porous network with a porosity as high as 80-99%, exhibiting extremely low thermal conductivity (as low as 0.013 W / (m·K)) and extremely low density. However, these materials are prepared by the sol-gel method, and the aerogel precursors used are mostly organosilicon sources. The synthesis process is complex, time-consuming, and costly. In addition, they have low mechanical strength, high brittleness, are difficult to mold, and have limited long-term temperature resistance, which restricts their large-scale application.

[0004] Fumed silica has a low bulk density and contains numerous mesoporous structures with pore sizes much smaller than the mean free path of air molecules at room temperature. This effectively suppresses heat transfer in the gas phase, and its thermal conductivity remains at 0.020~0.030 W / (m·K) even at 600°C. Its insulation performance far surpasses that of traditional inorganic insulation materials, making it a commonly used carrier for lightweight nanomaterials. However, when used for extended periods at 800°C, the high surface activity of the nanoparticles leads to interparticle sintering, decreased porosity, a sharp increase in thermal conductivity, and a significant degradation in insulation performance. Summary of the Invention

[0005] In order to solve the above-mentioned problems in the prior art, the present invention provides a high-temperature resistant lightweight thermal insulation material, which has good high-temperature thermal stability and can maintain excellent thermal insulation performance in high-temperature application environments.

[0006] The first aspect of the present invention provides a high-temperature resistant lightweight thermal insulation material, comprising 65-80 wt% fumed nano-SiO2 powder, 5-15 wt% silica powder, 3-15 wt% metakaolin, 3-10 wt% high silica glass fiber, and 1-5 wt% calcium aluminate cement.

[0007] The metakaolin contains 50-56 wt% SiO2 and 40-45% Al2O3.

[0008] The content of silicon dioxide in the gas-phase nano-SiO2 powder is ≥99.8wt%.

[0009] The silicon micropowder contains ≥99.0 wt% silicon dioxide and has a particle size of 1-10 μm.

[0010] The high-silica glass fiber contains ≥96wt% silica and has a length of 3-30mm.

[0011] The high-temperature resistant lightweight insulation material also includes 1-10 wt% of a barrier agent.

[0012] The barrier agent is selected from SiC micro powder, Si3N4 micro powder, TiC micro powder, TiO2 micro powder, ZrO2 micro powder, and K2Ti6O. 13 At least one of whiskers.

[0013] A second aspect of the present invention also relates to a method for preparing the above-mentioned high-temperature resistant lightweight thermal insulation material, comprising the following steps: S1. Preparation of raw materials: Weigh out the following materials by weight percentage: fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber, calcium aluminate cement, and optional barrier agent. S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, and mix for the first time. After mixing, introduce steam into the mixer and mix again to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape to obtain a molded blank; S4. Drying and firing: Dry the molded blank after pressing in step S3, then heat it to 750~820℃ and keep it at that temperature for 1~3 hours.

[0014] In step S3, the drying temperature is 90~150℃; preferably, the drying temperature is 100~120℃.

[0015] In step S4, the heating rate is 5~20℃ / min; preferably, the heating rate is 5~15℃ / min.

[0016] Compared with the prior art, the high-temperature resistant lightweight thermal insulation material of the present invention has the following beneficial effects: The high-temperature resistant lightweight thermal insulation material of the present invention uses fumed nano-SiO2 powder as the matrix. By adding an appropriate amount of silicon micro powder and metakaolin, the shrinkage internal stress of the overall thermal insulation material can be offset or alleviated, the internal structure can be stabilized and the overall temperature resistance of the material can be improved, and the thermal insulation performance under high temperature conditions can be maintained. Attached Figure Description

[0017] Figure 1 This is a SEM image of the high-temperature resistant lightweight thermal insulation material of the present invention. Figure 2 This is a diagram showing the internal structure of the high-temperature resistant lightweight thermal insulation material of the present invention. Detailed Implementation

[0018] To make the objectives, technical solutions, and technical effects of the present invention clearer, the technical solutions of the present invention will be further described below in conjunction with the accompanying drawings and embodiments. However, it should be stated that the accompanying drawings and embodiments are not intended to limit the scope of protection of the present invention.

[0019] The high-temperature resistant lightweight thermal insulation material of this invention comprises 65-80 wt% fumed nano-SiO2 powder, 5-15 wt% silica powder, 3-15 wt% metakaolin, 3-10 wt% high-silica glass fiber, and 1-5 wt% calcium aluminate cement. The high-temperature resistant lightweight thermal insulation material of this invention uses fumed nano-SiO2 powder as a matrix, where fumed silica can maintain its amorphous (non-crystalline) state well at high temperatures. It has an extremely low thermal conductivity, and the nano-sized primary particle aggregates form a large number of mesopores (2-50 nm), with pore sizes much smaller than the mean free path of air molecules at room temperature (~70 nm), effectively suppressing gas-phase heat transfer. Furthermore, its bulk density is extremely low (40-100 kg / m³), which can significantly reduce the structural load on kilns; it does not react with most media, has strong corrosion resistance, and high chemical inertness, making it suitable for acid and alkaline atmosphere conditions. However, when used for extended periods at 800°C, the high surface activity of the nanoparticles leads to interparticle sintering, decreased porosity, and a sharp increase in thermal conductivity, resulting in a significant degradation of thermal insulation performance. The silicon micropowder added in this invention contains over 99.0% SiO2, ensuring it reacts almost entirely with the matrix or other components at 800°C, acting as a "physical barrier." Furthermore, its high hardness, as a rigid particle, effectively resists the shrinkage stress generated by the sintering of gaseous nano-SiO2 powder, providing stable physical pinning. The silicon micropowder also has an extremely low coefficient of thermal expansion, with a linear expansion coefficient of only about 0.5~1.0×10⁻⁶. -6The temperature is / ℃, far lower than that of the gaseous SiO2 framework. Deformation during thermal cycling is minimal, effectively buffering thermal stress and preventing cracking due to expansion mismatch. Furthermore, its own thermal conductivity is low, having limited impact on overall thermal insulation performance. Adding an appropriate amount of silica powder to a gaseous nano-SiO2 matrix not only optimizes high-temperature mechanical properties but also mitigates the problem of nanoparticle agglomeration. Metakaolin, a dehydroxylated kaolin, is mainly composed of amorphous Al2O3·SiO2 active phase. It undergoes localized chemical bonding with the dangling bonds (≡Si-O·) on the surface of the gaseous nano-matrix SiO2, forming an Al-O-Si bridging structure. Combined with the use of silica powder, this significantly improves tensile strength, resisting sintering shrinkage driven by surface tension at firing temperatures below 820℃ and maintaining thermal insulation performance under high-temperature operating conditions.

[0020] In high-temperature operating environments (especially exceeding 600℃), the contribution of thermal radiation increases dramatically, even becoming the primary pathway for heat transfer. While the nanopores within the gas-phase nano-SiO2 powder matrix can suppress gas heat transfer, they are almost transparent to infrared radiation, allowing heat to directly "penetrate." Therefore, 1-10 wt% of an infrared blocking agent can be added. This infrared blocking agent is selected from SiC micro powder, Si3N4 micro powder, TiC micro powder, TiO2 micro powder, ZrO2 micro powder, and K2Ti6O. 13 At least one of the whiskers. The added infrared blocking agent can "block" the penetration of infrared heat by scattering and absorbing infrared radiation.

[0021] In this invention, the metakaolin contains 50-56 wt% SiO2 and 40-45% Al2O3. The fumed nano-SiO2 powder contains ≥99.8 wt% silica. The silica micropowder contains ≥99.0 wt% silica and has a particle size of 1-10 μm. The high-silica glass fiber contains ≥96 wt% silica and has a fiber length of 3-30 mm.

[0022] The high-silica glass fiber added in this invention acts as a skeleton dispersed in the matrix, which can not only disperse and transfer the load, significantly improve the tensile and bending strength, but also enable it to serve for a long time under high temperature conditions of 800°C, avoiding failure that could lead to material collapse and maintaining the overall thermal insulation performance of the material.

[0023] The preparation method of the above-mentioned high-temperature resistant lightweight thermal insulation material of the present invention includes the following steps: S1, raw material preparation: weigh fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber, calcium aluminate cement and optional barrier agent according to weight percentage for later use; S2, preparation of mixed raw materials: add the raw materials in step S1 to a mixer in sequence, mix for the first time, then introduce steam into the mixer and mix again to obtain the required mixed raw materials for later use; S3, pressing of mixed raw materials: press the mixed raw materials prepared in step S2 into a molded blank; S4, drying and firing: dry the molded blank after pressing in step S3, then heat it to 750~820℃ and keep it at that temperature for 1~3 hours. Figure 1 and Figure 2 SEM images and internal structure diagrams of the high-temperature resistant lightweight thermal insulation material of the present invention are shown respectively.

[0024] Example 1

[0025] The high-temperature resistant lightweight thermal insulation material of this embodiment comprises 65 wt% fumed nano-SiO2 powder, 10 wt% silica fume, 10 wt% metakaolin, 10 wt% high-silica glass fiber, and 5 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Preparation of raw materials: Weigh out the fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber and calcium aluminate cement by weight percentage for later use. S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours.

[0026] Example 2

[0027] The high-temperature resistant lightweight thermal insulation material in this embodiment includes 80wt% fumed nano-SiO2 powder, 5wt% silicon micropowder, 5wt% metakaolin, 5wt% high-silica glass fiber, and 3wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, silicon micro powder, metakaolin, high-silica glass fiber, and K2Ti6O. 13Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours.

[0028] Example 3

[0029] The high-temperature resistant lightweight thermal insulation material in this embodiment includes 75wt% fumed nano-SiO2 powder, 7wt% silica powder, 8wt% metakaolin, 5wt% high-silica glass fiber, and 3wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, silicon micro powder, metakaolin, high-silica glass fiber, and K2Ti6O. 13 Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours. Comparative Example 1

[0030] The high-temperature resistant lightweight thermal insulation material in this comparative example comprises 75 wt% fumed nano-SiO2 powder, 15 wt% silica micropowder, 5 wt% high-silica glass fiber, and 3 wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, silicon micro powder, high-silica glass fiber, and K2Ti6O. 13 Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours. Comparative Example 2

[0031] The high-temperature resistant lightweight thermal insulation material in this comparative example comprises 75 wt% fumed nano-SiO2 powder, 15 wt% metakaolin, 5 wt% high-silica glass fiber, and 3 wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, metakaolin, high-silica glass fiber, and K2Ti6O. 13 Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours.

[0032] The room temperature compressive strength, thermal conductivity at 800℃, linear shrinkage rate, and thermal conductivity at 800℃ after service (insulated at 800℃ for 200h) of the high-temperature resistant lightweight insulation materials of the examples and comparative examples were tested, and the results are shown in Table 1.

[0033] Table 1

[0034] The above description is only a preferred embodiment of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, they can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made without departing from the essential scope of protection claimed by the present invention shall fall within the protection scope of the present invention.

Claims

1. A high-temperature resistant lightweight thermal insulation material, characterized in that: It includes 65-80 wt% fumed nano-SiO2 powder, 5-15 wt% silica powder, 3-15 wt% metakaolin, 3-10 wt% high silica glass fiber, and 1-5 wt% calcium aluminate cement.

2. The high-temperature resistant lightweight thermal insulation material according to claim 1, characterized in that: The metakaolin contains 50-56 wt% SiO2 and 40-45% Al2O3.

3. The high-temperature resistant lightweight thermal insulation material according to claim 1, characterized in that: The content of silicon dioxide in the vapor-phase nano-SiO2 powder is ≥99.8wt%.

4. The high-temperature resistant lightweight thermal insulation material according to claim 1, characterized in that: The silicon micropowder contains ≥99.0 wt% silicon dioxide and has a particle size of 1-10 μm.

5. The high-temperature resistant lightweight thermal insulation material according to claim 1, characterized in that: The high-silica glass fiber contains ≥96wt% silica and has a length of 3-30mm.

6. The high-temperature resistant lightweight thermal insulation material according to claim 1, characterized in that: The high-temperature resistant lightweight insulation material also includes 1-10 wt% barrier agent.

7. The high-temperature resistant lightweight thermal insulation material according to claim 6, characterized in that: The barrier agent is selected from SiC micro powder, Si3N4 micro powder, TiC micro powder, TiO2 micro powder, ZrO2 micro powder, and K2Ti6O. 13 At least one of whiskers.

8. The method for preparing the high-temperature resistant lightweight thermal insulation material according to any one of claims 1 to 7, characterized in that... Includes the following steps: S1. Preparation of raw materials: Weigh out the following materials by weight percentage: fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber, calcium aluminate cement, and optional barrier agent. S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, and mix for the first time. After mixing, introduce steam into the mixer and mix again to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape to obtain a molded blank; S4. Drying and firing: Dry the molded blank after pressing in step S3, then heat it to 750~820℃ and keep it at that temperature for 1~3 hours.

9. The method for preparing the high-temperature resistant lightweight thermal insulation material according to claim 8, characterized in that: The drying temperature in step S3 is 90~150℃.

10. The method for preparing the high-temperature resistant lightweight thermal insulation material according to claim 8, characterized in that: In step S4, the heating rate is 5~20℃ / min.